Comprehensive Analysis of Circulating miRNAs in the Plasma of Patients With Pituitary Adenomas - Kinga Németh; Ottó Darvasi; István Likó; Nikolette Szücs; Sándor Czirják; Lilla Reiniger; Borbála Szabó; Lilla Krokker; Éva Pállinger; Péter Igaz; Attila Patócs; Henriett Butz (2019)
Abstract Background Circulating miRNAs in pituitary adenomas would improve patient care, especially as minimally invasive biomarkers of tumor recurrence and progression in nonfunctioning adenoma cases. Aim Our aim was to investigate plasma miRNA profiles in patients with pituitary adenomas. Materials and Methods A total of 149 plasma and extracellular vesicle (preoperative, early postoperative, and late postoperative) samples were collected from 45 patients with pituitary adenomas. Adenomas were characterized on the basis of anterior pituitary hormones and transcription factors by immunostaining. miRNA next-generation sequencing was performed on 36 samples (discovery set). Individual TaqMan assays were used for validation on an extended sample set. Pituitary adenoma tissue miRNAs were evaluated by TaqMan array and data in the literature. Results Global downregulation of miRNA expression was observed in plasma samples of pituitary adenomas compared with normal samples. Expression of 29 miRNAs and isomiR variants were able to distinguish preoperative plasma samples from normal controls. miRNAs with altered expression in both plasma and different adenoma tissues were identified. Three, seven, and 66 miRNAs expressed differentially between preoperative and postoperative plasma samples in GH-secreting, FSH/LH+, and hormone-immunonegative groups, respectively. miR‒143-3p was downregulated in late postoperative but not in early postoperative plasma samples compared with preoperative ones exclusively in FSH/LH+ adenomas. The plasma level of miR‒143-3p discriminated these samples with 81.8% sensitivity and 72.3% specificity (area under the curve = 0.79; P = 0.02). Conclusions Differentially expressed miRNAs in pituitary adenoma tissues have low abundance in plasma, minimizing their role as biomarkers. Plasma miR‒143-3p level decreased in patients with FSH/LH+ adenomas, indicating successful surgery, but its application for evaluating tumor recurrence needs further investigation.